The Competencies of Automotive Engineering Pre-Service Teachers - Mochammad Bruri Triyono, Gunadi, Herminanto Sofyan (International Journal of Advanced Science and Technology, 2020)
Teacher training institutions in Indonesia receives challenges in preparing candidates of qualified vocational teacher. Guiding teachers often complain about the quality of vocational teacher candidates who practice teaching in vocational schools. However, the competence of prospective vocational teachers from teacher training institutions is unknown. This study aims to describe the personal, social, professional, and pedagogic competence of pre-service students in Automotive Study Program of Universitas Negeri Yogyakarta (Indonesia) and identify the factors hindering the students’ teaching practicum program by using quantitative analysis. We show that by using the data from 47 teachers in 10 schools in Yogyakarta, the students’ scores at each section respectively are 77.12% (good) for personal, 75.08% (good) for social, 73.88% (good) for professional, and 71.95% (good) for pedagogic competence. The factors impeding the teaching practicum program consecutively include inappropriate schedule, which was too short and commenced in the middle of the semester, the students’ unpreparedness, and lack of knowledge of the school curriculum, teaching instruments, coordination among the lecturers and the guardian teachers, and school facilities.